Using Question Generation to Improve Reading Comprehension for Middle‐Grade Students. Issue 3 (8th November 2020) - Stevens, Elizabeth A.; Murray, Christy S.; Fishstrom, Sarah; Vaughn, Sharon
Abstract: Students in the middle grades are expected to read complex texts to acquire content knowledge, particularly in social studies/history and science. Most students with disabilities are included in social studies/history and science classes yet read below grade level, requiring significant support with accessing text knowledge. Question generation is one high‐impact, evidence‐based practice that content area teachers can use to support students as they read complex text. This practice has been studied in rigorous research studies, and findings suggest that students' reading comprehension increases when they apply the practice while reading. The authors provide an overview of question generation, including explanations of each step in the instructional process, so content area teachers can integrate this reading comprehension practice into their instruction.